1997
DOI: 10.1101/gad.11.10.1289
|View full text |Cite
|
Sign up to set email alerts
|

roughex down-regulates G2 cyclins in G1.

Abstract: Cell cycle arrest in G1 at the onset of patterning in the Drosophila eye is mediated by roughex. In roughex mutants, cells accumulate Cyclin A protein in early GI and progress into S phase precociously. When Roughex is overexpressed in S/G2 cells, Cyclin A is mislocalized to the nucleus and degraded, preventing mitosis. Whereas Roughex inhibits Cyclin A accumulation, Cyclin E down-regulates Roughex protein in vivo. Roughex binds to Cyclin E and is a substrate for a Cyclin E-Cdk complex in vitro. These data arg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
82
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(93 citation statements)
references
References 48 publications
11
82
0
Order By: Relevance
“…Therefore, the nuclear import of Cyclin A in ofs mutants was dissociated from other aspects of the G 2 -M transition. Similar precocious nuclear import had been observed upon overexpression of Roughex (Rux), a cyclin-dependent kinase inhibitor (Avedisov et al, 2000;Gönczy et al, 1994;Thomas et al, 1997). Indeed, we found that ofs mutant spermatocytes exhibited abnormal accumulation of Rux protein, and that Rux colocalized with nuclear Cyclin A (Fig.…”
Section: Off-schedule Identifies a Distinct Pathway Controlling Spermsupporting
confidence: 56%
“…Therefore, the nuclear import of Cyclin A in ofs mutants was dissociated from other aspects of the G 2 -M transition. Similar precocious nuclear import had been observed upon overexpression of Roughex (Rux), a cyclin-dependent kinase inhibitor (Avedisov et al, 2000;Gönczy et al, 1994;Thomas et al, 1997). Indeed, we found that ofs mutant spermatocytes exhibited abnormal accumulation of Rux protein, and that Rux colocalized with nuclear Cyclin A (Fig.…”
Section: Off-schedule Identifies a Distinct Pathway Controlling Spermsupporting
confidence: 56%
“…This phenotype is suppressed by the down-regulation of Cyclin A. Furthermore, overexpression of Rux protein induces degradation of Cyclin A and inhibits S-phase entry caused by Cyclin A accumulation (Sprenger et al, 1997;Thomas et al, 1997). Thus rux shares several features with ste9 and rum1; all proteins function as a negative regulator of G 1 progression.…”
Section: Discussionmentioning
confidence: 91%
“…The Drosophila roughex (rux) gene also controls cyclin A kinase activity in G 1 (Gö nczy et al, 1994;Thomas et al, 1994;Dong et al, 1997). Like the rum1⌬ mutant, rux mutant cells fail to arrest in G 1 , and they enter S-phase prematurely, with elevated cyclin A-associated kinase activity Sprenger et al, 1997;Thomas et al, 1997). rux may have a task similar to that of rum1 in fission yeast or SIC1 in budding yeast by preventing cyclin A from activating S-phase in early G 1 .…”
Section: Discussionmentioning
confidence: 99%